La migración española y el crecimiento agrícola del Valle de Constanza (1954-2003) - Ramírez de Haro, Gonzalo (Revista Española de Desarrollo y Cooperación, 2023)
More than four thousand Spanish peasants migrated to the Dominican Republic in the mid fifties of the last century, in the context of a colonization program implemented by the government of that country. They received land and working tools in different settlements, as well as other benefits. Nevertheless, a big proportion asked to return to Spain before long. In the course of time four of the five initial settlements were practically abandoned. But in the fifth (Constanza) there was an accelerated process of agricultural modernization, headed by the Spanish migrants, that implied the transfer of know-how to the local population. In this text, I explore the causes of the different path that was followed in Constanza and some of the consequences of the migration process in that area.